Advanced Manufacturing Technologies: Development and Prospect - Tibor Krenicky (Applied Sciences)
The main aim of this Special Issue was to present the current state of the research on the subjects of theory, modeling, monitoring, and control of the operation of technology systems and processes, along with research and diagnostics of manufacturing systems and processes operation. The contributions have focused on manufacturing research, operation reliability, and diagnostics of machines; inspection, measurements, evaluation, and diagnostics of production quality in technologies of standard and progressive machining; reversible engineering; 3D printing; pressure die casting; injection molding; EDM; AWJ cutting; etc., which are used for advanced processing of materials and various kinds of technological applications.